That is the way it is defined; in theory, it could be defined any other way. But the definition commonly used makes several rules maintain their validity, for example, the law about adding exponents - even when the exponent is negative.
Consider this sequence:
103 = 1000
102 = 100
101 = 10
100 = 1
10-1 = 1/10
10-2 = 1/100
Every time the exponent is reduced by one, the result gets reduced by a factor of 10. So, it seems logical to continue this pattern for a zero or negative exponent. Mind you, this is no proof - after all, the negative exponents is a matter of definitions, not of proof. The above only merely shows that the definition is reasonable.
That is the way it is defined; in theory, it could be defined any other way. But the definition commonly used makes several rules maintain their validity, for example, the law about adding exponents - even when the exponent is negative.
Consider this sequence:
103 = 1000
102 = 100
101 = 10
100 = 1
10-1 = 1/10
10-2 = 1/100
Every time the exponent is reduced by one, the result gets reduced by a factor of 10. So, it seems logical to continue this pattern for a zero or negative exponent. Mind you, this is no proof - after all, the negative exponents is a matter of definitions, not of proof. The above only merely shows that the definition is reasonable.
That is the way it is defined; in theory, it could be defined any other way. But the definition commonly used makes several rules maintain their validity, for example, the law about adding exponents - even when the exponent is negative.
Consider this sequence:
103 = 1000
102 = 100
101 = 10
100 = 1
10-1 = 1/10
10-2 = 1/100
Every time the exponent is reduced by one, the result gets reduced by a factor of 10. So, it seems logical to continue this pattern for a zero or negative exponent. Mind you, this is no proof - after all, the negative exponents is a matter of definitions, not of proof. The above only merely shows that the definition is reasonable.
That is the way it is defined; in theory, it could be defined any other way. But the definition commonly used makes several rules maintain their validity, for example, the law about adding exponents - even when the exponent is negative.
Consider this sequence:
103 = 1000
102 = 100
101 = 10
100 = 1
10-1 = 1/10
10-2 = 1/100
Every time the exponent is reduced by one, the result gets reduced by a factor of 10. So, it seems logical to continue this pattern for a zero or negative exponent. Mind you, this is no proof - after all, the negative exponents is a matter of definitions, not of proof. The above only merely shows that the definition is reasonable.
Chat with our AI personalities
That is the way it is defined; in theory, it could be defined any other way. But the definition commonly used makes several rules maintain their validity, for example, the law about adding exponents - even when the exponent is negative.
Consider this sequence:
103 = 1000
102 = 100
101 = 10
100 = 1
10-1 = 1/10
10-2 = 1/100
Every time the exponent is reduced by one, the result gets reduced by a factor of 10. So, it seems logical to continue this pattern for a zero or negative exponent. Mind you, this is no proof - after all, the negative exponents is a matter of definitions, not of proof. The above only merely shows that the definition is reasonable.
Yes. Any multiplication involving an odd number of negative operands will be negative (assuming non-zero operands).
When a number is raised to a negative exponent, it means the reciprocal of that number raised to the positive exponent. Therefore, 5 to the power of -1 is equal to 1/5, or 0.2. This is because any number raised to the power of -1 is the multiplicative inverse of that number, which is the reciprocal.
10 to the negative 1 is equal to 1 divided by 10, which simplifies to 0.1. This is because any number raised to the power of -1 is the reciprocal of that number. In this case, the reciprocal of 10 is 1/10 or 0.1.
The multiplication rule of thumb always states that a negative number times a negative number results in a positive number. Since an even number is always divisible by two, any value raised to an even integer power will result in a positive number. However, a basic proof is presented as follows: (-A) * (-A) = A^2 ((-A) * (-A)) ^ 2 = ((-A * -A) * (-A * -A)) = A^2 * A^2 = A ^ 4 ...
Any number raised to the power 1 is that same number, x1 = x. For example, 51 = 5.